Optimalisasi Peran Saksi Perkawinan dalam Pengembangan Iman Keluarga Muda Katolik: Studi Kasus Kelompok Umat Basis St. Louise Maria De Montfort - Silfester Oktovius Rewak Hipir (JURNAL PASTORAL KATEKETIK, 2025)
Catholic marriage is a sacrament requiring continuous accompaniment for young families living their faith amid contemporary challenges. This research analyzes the role of marriage witnesses in developing young Catholic families' faith and formulates optimization strategies. The study employs qualitative approach with case study method at Basic Ecclesial Community (KUB) St. Louise Maria de Montfort, Santa Maria Assumpta Parish. Data were collected through in-depth interviews, observation, and document analysis involving 15 informants: 5 young couples, 5 marriage witnesses, and 5 pastoral figures. Results show marriage witnesses' role remains symbolic and ceremonial, not yet maximized as active pastoral companions. Main obstacles include lack of witness training, absence of systematic accompaniment guidelines, and minimal synergy between Church structures and KUB. However, significant potential exists among witnesses with spiritual experience and active Church involvement. Research recommends developing special formation programs for marriage witnesses, creating family faith accompaniment modules based on local needs, and strengthening pastoral cooperation to optimize witnesses' function in accompanying young Catholic families' faith growth.